Precision photothermal therapy and photoacoustic imaging by in situ activatable thermoplasmonics. Issue 29 (5th July 2021) - Liu, Yahua; Mo, Fengye; Hu, Jialing; Jiang, Qunying; Wang, Xiuyuan; Zou, Zhiqiao; Zhang, Xian-Zheng; Pang, Dai-Wen; Liu, Xiaoqing
Abstract : A tumor microenvironment-activated photoagent is reported for precise photothermal therapy and photoacoustic imaging via controllable thermoplasmonics. The agent can sensitively image tumors and lymph node metastasis and specifically ablate tumors. Abstract : Phototherapy holds great promise for disease treatment; however, traditional "always-on" photoagents have been restricted to clinical translation due to their nonspecific response and side effects on normal tissues. Here, we show a tumor microenvironment activated photothermal and photoacoustic agent as an activatable prodrug and probe that allows precise cancer diagnosis and treatment. Such an in situ revitalized therapeutic and contrast agent is achieved via controllable plasmonic heating for thermoplasmonic activation. This enables monitoring of signal molecule dynamics, real-time photothermal and photoacoustic imaging of tumors and lymph node metastasis, and targeted photothermal therapy without unwanted phototoxicity to normal tissues. Our study provides a practical solution to the non-specificity problem in phototherapy and offers precision cancer therapeutic and theranostic strategies. This work may advance the development of ultrasensitive disease diagnosis and precision medicine.